Model-based optimization of heat recovery in the cooling zone of a tunnel kiln - MANÇUHAN, EBRU; KÜÇÜKADA, KURTUL (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
A mathematical model representing the phenomena of heat transfer and fluid flow was developed to compute the state variables such as the air mass flow rate, brick and air temperatures along the cooling zone of a tunnel kiln. Using the mathematical model, the optimization of the cooling zone was realized to minimize the pressure drop by finding the optimum suction and blowing air flow rate profiles in addition to the ambient air flow rate entering from the brick exit side. The optimization was realized by considering the cooling zone as a decomposable structured system formed of N interconnected cells. The plant data were used to compare with the model-based optimization results. The measured temperatures from the cooling zone are practically values between the brick and air temperatures. The results showed that the minimum pressure drop was obtained by considering the tunnel kiln cooling zone composed of two regions of suction and two regions of blowing while satisfying the process constraints. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: tunnel kiln; cooling zone; heat recovery; model-based optimization